Obsolete Muskets, Lethal Remingtons: Heterogeneity and Firepower in Weapons of The Frontier War, Argentina, 1869–1877 - Leoni, Juan Bautista (2014)
Fil: Fil: Leoni, Juan Bautista. CONICET. University of Buenos Aires. Institute of Archaeology. Buenos Aires; Argentina